MANAJEMEN PEMBELAJARAN PKN DENGAN LIGHTENING THE LEARNING CLIMATE - Syahruddin Syahruddin (UNIVERSITAS BENGKULU, 2017)
The purpose of this research is: (a) To reveal the learning management of Civics with Lightening the Learning Climate on the results of learning Civics. (b) To reveal the management of Civics learning with Lightening the Learning Climate on the motivation to learn Civics. This research uses action research for three rounds. Each round consists of four stages: design, activity and observation, reflection, andrefficiency. The target of this research is the students of Class VIII.c Data obtained in the form of formative test results, observation sheet of teaching and learning activities. From the analyst's result, it is found that the students' learning achievement has improved from cycle I to cycle III that is, cycle I (25%), cycle II (61,11%), cycle III (83,33%). The conclusion of this research is the learning of Civics Management with Lightening the Learning Climate can have a positive effect on student learning motivation.